Functions Associated with $^*g \hat{α}$-Closed Sets in Topological Spaces - S. Pious Missier; K. M. Arifmohammed (International Journal of Mathematics And its Applications, 2018)
In this paper, we introduce $^*g \hat{α}$-continuous maps and study their relation with various generalized continuous maps. We also discuss certain properties of $^*g \hat{α}$-continuous maps. We then introduce $^*g \hat{α}$-irresolute maps, strongly $^*g \hat{α}$-continuous maps and perfectly $^*g \hat{α}$-continuous maps in topological spaces and some properties of these maps are discussed.